Emerging Pollutants in Moroccan Wastewater: Occurrence, Impact, and Removal Technologies. (25th January 2022) - Jari, Yassine; Roche, Nicolas; Necibi, Mohamed Chaker; El Hajjaji, Souad; Dhiba, Driss; Chehbouni, Abdelghani
Abstract : The rapid growth of anthropogenic activities in recent decades has resulted in the appearance of numerous new chemical compounds in the environment, known as "emerging pollutants" (EPs) or "contaminants of emerging concern" (CECs). Although partially or not yet regulated or monitored, there is growing research interest in these EPs among the scientific community because of their bioaccumulation, persistence, and adverse effects. Among these, endocrine disruptors, pesticides, and pharmaceuticals can have harmful impacts on human health and the ecosystem. Conventional wastewater treatment technologies are not effective in removing these contaminants, allowing them to be released into the receiving environment. In order to improve the understanding of emerging pollutants, this review discusses the source, occurrence, and impacts of bisphenol A, atrazine, amoxicillin, and paracetamol as model molecules of emerging environmental pollutants, an issue that remains underrepresented in Morocco. Then, treatment methods for EPs are reviewed, including adsorption, advanced oxidation processes, biodegradation, and hybrid treatment. It is proposed that adsorption and photocatalysis can be used as simple, effective, and environmentally friendly technologies for their removal. Thus, we summarize some of the adsorbent and photocatalyst materials applied in recent work to control these pollutants. Towards the end of this paper, the development of inexpensive and locally available (Morocco) materials to remove these compounds from wastewater is considered.